Landscapes of Human Evolution : Contributions in Honour of John Gowlett. - Cole, James (Archaeopress archaeology., 2020)
Fourteen papers are presented here in honour of John Gowlett. John has a wide range of research interests primarily focused on the human genus Homo and is a world leader in understanding the cognitive and behavioural preconditions necessary for the emergence of complex behaviours such as language and art.